O Programa Bolsa Família e a oferta de trabalho: uma perspectiva de choque orçamentário - Clarissa Gondim Teixeira (2009)
This thesis proposes an in-depth study of the relation between cash transfers and supply of labor hours. Despite the strong evidence that Conditional Cash Transfer Programs (CCT) have a positive effect in various aspects of well-being, they are frequently questioned about a possible perverse effect on labor supply. A reduction of overall labor supply would threaten CCT goals of short run poverty alleviation and to break intergenerational poverty in the long run.Cash transfers are here understood as income shocks that have a range of intensities measured by transfer per capita. The main hypotheses to be tested are: 1) increases in household income through non labor income source diminishes supply of labor hours for occupied adults; 2) income shock intensity is relevant and changes the effect cash transfers promotes; 3) self-employed workers react differently than paid workers because the first ones might invest part of the transfer into their production. The supply of labor hours of occupied men and women who live in households eligible to the Bolsa Família Program (PBF) was analyzed using the National Household Survey (PNAD) year 2006, by the Brazilian Institute of Geography and Statistics (IBGE). The Generalized Propensity Score Method was used in order to encompass the dose-effect concept. The Average Treatment Effect on the Treated (ATT) measure lead to the conclusion that PBF marginally diminishes the supply of work hours of occupied adults. Change in work hours varies according to transfer value and income shock intensity. Moreover, there are evidences that self-employed agricultural workers react differently from self-employed non-agricultural workers and informal workers. The impact is more expressive for informal workers, women, low paid workers, and the ones whose wage represents a smaller share of total household income, that is, the other members apart the household leader.From the results it is possible to conclude that there is no adverse effect. The impact is consequence of household utility maximization. Previous literature shows no consistent significant impact in labor market participation and the findings of the effect on labor hours for occupied adults only occurs marginally so that it represents no threat to Bolsa Família objectives.